Phenomenology Study: Resilience of Farmers About Natural Disaster - Deviantony, Fitrio (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Floods and landslides are disasters that cause a lot of damage related to the neighborhood, and there is anincreasing number of morbidity, as well as the amount of damage from the environment that occurs, and otherimpacts will undoubtedly affect the psychology of the communities affected by the disaster. The psychologicaleffect of this unusual event will undoubtedly lead to trauma or the so-called posttraumatic stress disorder(PTSD). This study was aimed to explore the experiences of farmers who experienced direct floods andlandslides; the research design was used is a qualitative research design using an interpretativephenomenology approach. The technique of collecting data used in-depth interviews with a semi-structuredinterview guide involving five participants, and the data were analyzed using interpretative phenomenologyanalysis. This research was conducted on six themes. First was disasters caused by humans, and the secondtheme was accepting the existing reality, the third theme is getting closer to God, the fourth theme has thedesire to farm again after the disaster, the fifth theme was restoring the family economy, the sixth theme waskeeping the environment around and improving themselves.